The Results of Two-stage Revision for Methicillin-resistant Periprosthetic Joint Infection (PJI) of the Hip. Issue 5 (28th May 2020) - Santoso, Asep; Anwar, Iwan Budiwan; Sibarani, Tangkas SMHS; Soetjahjo, Bintang; Yoon, Taek-Rim; Park, Kyung Soon
Patellar tendon rupture after total knee arthroplasty is a rare, but often catastrophic complication. In addition, infection is also a dreaded complication after total knee arthroplasty. We report an 84-year-old female that has late infected total knee arthroplasty with patellar tendon rupture treated with resection arthroplasty and then subsequent arthrodesis with retrograde intramedullary nail. Objective: Periprosthetic joint infection (PJI) of the hip due to methicillin-resistant bacteria is difficult to treat and remain a challenge for arthroplasty surgeon. Methods: Retrospective review was done to the patients who received two-stage revisions with antibiotic loaded cement-spacer for PJI of the hip between January 2010 to June 2015. We found 65 patients (65 hips) with positive culture findings. Eight patients were lost to followup and excluded from the study. Among the rest of the 57 patients, methicillin-resistant infection (MR Group) was found in 28 cases. For comparison, we also evaluated the 29 other cases that caused by other pathogen (Non-Methicillin resistant group/Non-MR group). We compared all of the relevant medical records and the treatment outcomes between the two groups. Results: The mean of follow-up period was 33.7 months in the methicillin-resistant group and 28.4 months in the nonmethicillin-resistant group (p = 0.27). The causal pathogens in the methicillin-resistant group were: Methicillin-resistant Staphylococcus aureus (MRSA) in 10 cases, Methicillin-resistant Staphylococcus epidermidis (MRSE) in 16 cases and Methicillin-resistant coagulase-negative Staphylococcus (MRCNS) in 2 cases. The reimplantation rate was 92.8% and 89.6% in the methicillin-resistant and nonmethicillinresistant groups, respectively (p= 0.66). The rates of recurrent infection after reimplantation were 23.1% (6/26) in the methicillin-resistant group and 7.6% (2/26) in the nonmethicillinresistant group (p= 0.12). The overall infection control rate was 71.4% (20/28) and 89.6% (26/29) in the methicillin-resistant and nonmethicillin-resistant groups, respectively (p = 0.08). Both group showed comparable baseline data on mean age, BMI, gender distribution, preoperative ESR/CRP/WBC and comorbidities. Conclusion: Two-stage revision still resulted a higher recurrency rate and lower infection control rate for the treatment of periprosthetic joint infection (PJI) of the hip due to methicillin-resistant infection compared to nonmethicillin-resistant infection.